Perceptions of blood donation among the students of Jahangirnagar University, Bangladesh - Salma, Nahid (Asian Journal of Medical and Biological Research, 2021)
Each year, millions of lives are saved through blood transfusion. Most of the youngsters are the potential voluntary and replacement blood donors in every society where students comprise significant amount. By knowing their perceptions about blood donation and by encouraging them to donate blood regularly will help to fulfill the demand of safe blood. Therefore, the research aimed to know the perceptions of university students towards blood donation and to explore the factors influencing their willingness to donate blood. Using convenient sampling, the data were collected from 201 current students of Jahangirnagar University through a well-structured questionnaire. Results show, the blood donation rate is quite good among students of Jahangirnagar University of Bangladesh (50.74%) and most of them are male (80.39%) compared to female (19.61%). The study revealed students “mother’s education level”, “residence type”, “number of blood donating times” and “involvement with blood donation organization” are highly significant factors with their blood donation behavior (p <0.001). About 67% student donated their blood to save another life and 28% blood donor think, it is their social responsibility. Five reasons found behind not donating blood: health (71%) had no time (14%), no reason (6%) for fear (8%) and religion (1%). Though half of the university students donate blood but by introducing more motivational campaign by government or blood donation organization or university authority, rest of the students attitude can be converted, and they may donate blood which will help to fulfill Bangladesh’s annual safe blood demand. Asian J. Med. Biol. Res. 2021, 7 (4), 339-347